Building ethical organisation cultures – Guidelines from Indian ethos. (15th April 2009) - Sivakumar, N.; Rao, U.S.
Organisation culture represents the core values, beliefs and attitudes in an organisation. An ethical organisation culture is a culture, which supports and promotes ethical behaviour in the organisation. Organisation cultures which promote ethical behaviour have become important in the context of large scale unethical behaviour in business and other organisations. Building an ethical organisation culture requires several aspects to be put into proper place. It requires clearly defining the core values of the organisation, selecting appropriate personnel, rewarding ethical behaviour and keeping checks on unethical behaviour. This article delineates the guidelines for building such organisation cultures as provided in Indian ethos. A wide range of Indian scriptures related to management and administration have been studied to explain the guidelines provided regarding various aspects of building ethical organisation cultures. After providing a brief review of relevant literature, the article explains the guidelines provided in the scriptures under different aspects of building ethical organisation cultures.